Update on the Application of Ultrasonography in Understanding Autosomal Dominant Polycystic Kidney Disease - Wen-Chin Lee; Ben-Chung Cheng; Chien-Te Lee; Shang-Chih Liao (Journal of Medical Ultrasound, 2024)
With an estimated prevalence of 1 in 1000 individuals globally, autosomal dominant polycystic kidney disease (ADPKD) stands as the most prevalent inherited renal disorder. Ultrasonography (US) is the most widely used imaging modality in the diagnosis and monitoring of ADPKD. This review discusses the role of US in the evaluation of ADPKD, including its diagnostic accuracy, limitations, and recent advances. An overview of the pathophysiology and clinical manifestations of ADPKD has also been provided. Furthermore, the potential of US as a noninvasive tool for the assessment of disease progression and treatment response is examined. Overall, US remains an essential tool for the management of ADPKD, and ongoing research efforts are aimed at improving its diagnostic and prognostic capabilities.